IPO ČSOB - Ondová, Michaela (2010)
The thesis aims to apply the theoretical approach of IPOs and financial services firm valuation on the Czech subsidiary of KBC: ČSOB. The theoretical part reviews the process of IPO with typical features of IPOs, and the pricing of IPO is discussed with the focus on theory of banks valuation. The empirical part of the thesis provides a financial analysis of the ČSOB, business plan and the valuation of the bank as of 30 September 2010 with the price of the actual IPO. This part aims at practical application of the theory of IPO and valuation. Al in all, the aim of the thesis is to apply theoretical knowledge of the IPOs on the practical case of ČSOB. Various analyses such as of KBC, ČSOB, Czech banking market, development of IPOs in CEE are used in order to apply and determine the reasons for the IPO, its timing, price and potential structure of investors.